PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA KELAS X INSTALASI TENAGA LISTRIK - Givson H. Siregar; Hamonangan Tambunan (Universitas Negeri Medan, 2021)
Abstract This research was conducted to find out whether there is an influence of the Discovery Learning learning model on student learning outcomes in the basic subjects of electricity and electronics for class X electrical power installations (TITL) in Vocational Schools for the 2019/2020 school year. This type of research is factorial. The population in this study were students of class X TITL SMK Negeri 1 Percut Sei Tuan and class X TITL students of SMKN 5 Medan. The sample of this study consisted of 2 classes, namely the experimental class which was taught using the Discovery Learning model and the control class which was taught using the Expository learning model. The data collection technique is done by using a test technique using multiple choice questions that have been tested for validity, reliability, level of difficulty and differentiating power of questions. The results showed that the results of hypothesis testing with the t-Ha test were accepted, there was an influence on the basic learning outcomes of electricity and electronics using the Discovery Learning learning model. Keywords: Discovery Learning Learning Model, Expository, Learning Outcomes. AbstrakPenelitian ini dilakukan untuk mengetahui apakah ada pengaruh model pembelajaran Discovery Learning terhadap hasil belajar siswapada mata pelajaran dasar listrik dan elektronika kelas x instalasi tenaga listrik (TITL) di SMK tahun ajaran 2019/2020. Jenis penelitian ini adalah Faktorial. Populasi dalam penelitian ini adalah siswa kelas X TITL SMK Negeri 1 Percut Sei Tuan dan siswa kelas X TITL SMKN 5 Medan. Sampel penelitian ini sebanyak 2 kelas yaitu kelas eksperimen yang diajarkan dengan menggunakan model pembelajaran Discovery Learning dan kelas kontrol yang diajarkan dengan model pembelajran Ekspositori. Teknik pengumpulan data dilakukan dengan teknik tes menggunakan soal pilihan ganda yang telah teruji validitas, realibilitas, tingkat kesukaran dan daya beda soal. Hasil penelitian menunjukkan bahwa hasil uji hipotesis dengan uji t Ha diterima, terdapat pengaruh hasil belajar dasar listrik dan elektronika dengan menggunakan model pembelajaran Discovery Learning. Kata kunci : Model Pembelajaran Discovery Learning, Ekspositori, Hasil Belajar